'Redeemed' or 'isolated': A systematic review of the experiences of older adults receiving a mild cognitive impairment diagnosis. - Ma, Jingya; Zhang, Huan; Li, Zheng (Geriatric Nursing, 2023)
• Cognitive decline not only severely affects the quality of life of older adults and their daily living ability, but also increases their risk of developing dementia. • Early assessment and diagnosis of MCI can help older adults clearly understand their condition, identify risk factors for cognitive decline, and access medical resources or treatment. • This review revealed that the experiences of being diagnosed with MCI in older adults presented three distinct process characteristics from the initial intricate understanding of the diagnosis, followed by a series of emotional and psychological reactions, and then coped with it in varied and different ways. Understanding the experiences of older adults living with MCI can benefit healthcare professionals in diagnosing and implementing early interventions to delay cognitive decline. To assess and synthesize qualitative research exploring the experience of older adults diagnosed with MCI. PubMed, Embase, CINAHL, Web of Science, and PsycINFO databases were searched. Studies involving the experience of being diagnosed with MCI in older adults were included. Thomas and Harden's methodology of synthesizing qualitative studies was used. Eleven studies were included. Three themes were identified: perceived reality of the MCI diagnosis; emotional and psychological responses to the MCI label; coping engaged in parallel processing. Older adults had confusing perspectives on the MCI diagnosis, leading to complicated and diverse emotional reactions and coping measures. The relationship between perspectives, emotional reactions, and coping methods might be the key for healthcare professionals to break through the early diagnosis and intervention of MCI.